Water Nationalization and Service Quality - Borraz, Fernando; Gonzalez Pampillon, Nicolas; Olarreaga, Marcelo (Oxford University Press on behalf of the World Bank, 2015)
The objective of this paper is to explore the impact of Uruguay's privatization and subsequent nationalization of water services on network access and water quality. The results suggest that although the early privatization of water services had little impact on access to the sanitation network; the subsequent nationalization led to an increase in network access at the bottom of the income distribution as well as an improvement in water quality.